ANALISIS HUBUNGAN PENGALAMAN ORGANISASI, EVALUASI TERHADAP KINERJA DAN HASIL KARIR AUDITOR PADA KAP : PENGUJIAN PENGARUH GENDER - Murtanto .; Mery Andryani (Media Riset Akuntansi, Auditing & Informasi, 2005)
This research observed the effect of gender difference to the organizational expe-rience, performance evaluation and career outcomes in accounting firm. This research also observed the relationship between variable of organizational experience and variable of performance evaluation, and relationship between variable of performance evaluation and variable of career outcomes. The integration is put into research model that was adopted from Greenhouse et al. (1990).The samples of this research are auditors and supervisors working in major account-ing firm. Data from the samples were obtained through questionnaires. The test of hypothesis used Analysis of Variance (ANOVA) and correlation test.The result of the research shows that in terms of organizational experience, perfor-mance evaluation and career outcomes, there is no significant difference between male auditor and female auditor. The research test indicates that there is a positive correlation between variable of organizational experience and variable of performance evalua-tion, and also between variable of performance evaluation and variable of career outcomes.Keywords: gender, job satisfaction, organization accountant, career outcomes.